New Evidence on Financial Incentives and the Timing of Retirement - Barbara Hanel; Regina T. Riphahn (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
We investigate the responsiveness of individual retirement decisions to changes in financial incentives. The causal effect is identified based on the natural experiment generated by an institutional reform. The results of a binary retirement model are robust to alternative model specifications, to a competing risks framework with endogenous panel attrition, and to alternative representations of unobserved individual-specific heterogeneity. We find strong behavioral effects of changes in financial retirement incentives. A permanent reduction of retirement benefits by 3.4 percent induces a decline in the age-specific annual retirement probability by over 50 percent. The response to the reforms intensifies over time suggesting that retirement behavior may be affected by social norms. The response to changes in financial retirement benefits varies with educational background: those with low education respond most strongly to an increase in the price of leisure.
Keywords: J26; H55; J14; 330; retirement insurance; incentives; social security; labor force exit; natural experiment; Switzerland